Qualidade da gestão pedagógica no curso de pedagogia - Lunardi, Elisiane Machado (2012)
This study inserts itself on the research line "Formation, Policies and Practices in Education from the PPGEdu/PUCRS and is part of the set of works and researches produced in the CEES - Center for Studies in Higher Education/PUCRS. It has as main objective to recognize the indicators of quality related to the pedagogical management of the Pedagogy Course of a Community Higher Education Institution (HEI) from Santa Maria, RS. The specific objectives consisted in: to identify which dimensions and indicators are related to the quality of pedagogical management of the Pedagogy Course; to identify concepts of quality of the pedagogical management in the Pedagogy Course; to perform intersection between pedagogical management and quality in the higher education. This study is a research with a qualitative approach, by means of a case study in a Pedagogy Course prior mentioned. The subjects target of the research were sixteen (16) teachers, including one (1) manager of Pro-rector Undergraduate (PROGRAD) and two (02) management and teachers of the Pedagogy Course. The theoretical contributions are anchored mainly on authors such as: Morosini (2001, 2003, 2004, 2005, 2006, 2008, 2009, 2010), Isaia and Bolzan (2008, 2009, 2010), Juliatto (2005), Libâneo ( 2000, 2006), Pepper and Anastasiou (2002, 2010), Tardif (2000, 2002, 2012), Rivers (2008, 2010), Zabalza (2004), Gauthier (1998), Cunha (2002, 2004, 2006, 2010). Data analysis endorses the following thesis: the thesis that the pedagogical management of quality of the Pedagogy Course is related to formation trajectories and professional development, classroom management, organizational culture of HEI and of the course, in its relationships with national and international public policies. Among the dimensions found, it is possible to highlight: careers and professional development of the teachers solid formation, continued formation, teaching production, different knowledge and practices of the teaching and valorization of the salary; organizational culture of the institution - work regime, administrative and pedagogical meetings, organizing of activities in the course, infrastructure of the institution, community service, educational performance - teaching role; sharing knowledge and practices, participative management, innovation and ethics; classroom management in the course of pedagogy - teaching inseparability between theory and practice, diversity and valuing of the differences, interdisciplinary activities and formative assessment. Therefore, the quality of the pedagogical management of UNIFRA Pedagogy Course is anchored in institutionalized pedagogy, and at the same time, to knowledge of each teacher. In the intersection of different contexts, the pedagogical management is being formed based on from the collective to the individual, and vice versa, based on a simultaneous movement of interrelation between teaching trajectories, organizational culture of the HEI and the performance of teacher educators of the Pedagogy Course observed the national and international public policies.